2021
DOI: 10.4062/biomolther.2021.086
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Digestive Disorders: Advances in Understanding and Therapeutic Approaches

Abstract: The gastrointestinal (GI) tract is a series of hollow organs that is responsible for the digestion and absorption of ingested foods and the excretion of waste. Any changes in the GI tract can lead to GI disorders. GI disorders are highly prevalent in the population and account for substantial morbidity, mortality, and healthcare utilization. GI disorders can be functional, or organic with structural changes. Functional GI disorders include functional dyspepsia and irritable bowel syndrome. Organic GI disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 144 publications
(129 reference statements)
0
5
0
1
Order By: Relevance
“…The dysfunctional autophagy mechanism leads to intestinal barrier injury and chronic intestinal inflammation in humans and animals. 68,69…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysfunctional autophagy mechanism leads to intestinal barrier injury and chronic intestinal inflammation in humans and animals. 68,69…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunctional autophagy mechanism leads to intestinal barrier injury and chronic intestinal inflammation in humans and animals. 68,69 The protective effects of resveratrol treatment during different kinds of disorders and diseases have been widely reported to associate with its regulatory role on autophagy and mitophagy, involved in several cell signaling molecules like p62, AMPK, SIRT-1 and other targets. [70][71][72][73][74] However, few research studies focus on resveratrol's regulatory effect on the autophagy pathway to mediate intestinal physiological function 23,75 and the underlying mechanism remains unclear.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Autophagy disorders have been implicated in the pathogenesis of various digestive diseases, including pancreatitis, IBD, colon cancer, and liver diseases [ 165 ]. S1P receptors are widely expressed in the digestive system and play different roles in autophagy regulation.…”
Section: S1p-mediated Autophagy Regulation In Diseasesmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is characterized with abnormal inflammatory and immune responses in the intestine [73,74]. Genome-wide associated investigations indicated that numerous canonical autophagy genes have involve in IBD [75,76].…”
Section: Alternative Regulated Inflammatory Bowel Diseasementioning
confidence: 99%